Ola Rotimi’s “The Gods are not to Blame” and Modeling of Leadership and Nation-building in a Nigerian Language Arts Classroom Situation - Morah, Ita, Peter; Agbo, Ochagu, Kaka; Ekahe, Nchor, Emmanuel; Ashiwel, Ugbe, Gregory (Recent Trends in Arts and Social Studies Vol. 3, 2023)
No nation can grow above the level of her education. This means education is the pivot for national development. Consequently, classrooms are ready incubators for leadership and nation-building training. One of such classrooms that readily has such potentials is the language arts classroom. This is where texts of didactic components are explicated, and morals drawn out, which are entrusted in the students for self and national benefits. This work attempts to use Ola Rotimi’s The gods are not to blame to demonstrate how literary texts can be employed to teach students, who are potential leaders, to acquire leadership skills and use them for nation-building.